Self-Assessment in Managing for Results: Conducting Self-Assessment for Development Practitioners - Rodriguez-García, Rosalía (Washington, DC: World Bank, 2012)
This paper proposes a systematic and pragmatic approach to planning and conducting self-assessments of country and program strategies. The approach, which is grounded on inquiry principles and guided by a sound and logical conceptual model and process, is applicable to strategy development, progress reviews, and program management. The authors have used the approach in various settings-in the public and private sectors, in academic institutions, and in nongovernmental organizations (NGOs). This paper argues that the self-assessments it describes can make three strategic contributions. First, they use a participatory process, which engages those responsible for designing and implementing strategies and programs in the assessment process. Second, they improve strategy design by providing critical information that can be used for finetuning and further developing the strategy. Third, they focus on the outcomes that have been achieved during the program period, triangulating multiple data sources to assess progress, and deriving lessons that can be incorporated in the next program strategy. Thus, these self-assessment exercises become powerful tools in planning and managing for results at the operational level, and an important source of learning about achievements across sectors and countries.